The Central Park Five - Burns, Ken 1953-; McMahon, David; Burns, Sarah (2013)
"In 1989, five black and Latino teenagers from Harlem were arrested and later convicted of raping a white woman in New York City's Central Park. They spent between 6 and 13 years in prison before a serial rapist confessed that he alone had committed the crime, leading to their convictions being overturned. Set against a backdrop of a decaying city beset by violence and racial tension, The Central Park Five tells the story of that horrific crime, the rush to judgment by the police, a media clamoring for sensational stories and an outraged public, and the five lives upended by this miscarriage of justice." [cover]
Englisch - Untertitel: Englisch, Spanisch
Original: USA 2013
Special features: interview with the filmmakers ; after the Central Park Five
Bildformat 16:9 widescreen
Keywords: Film; DVD-Video